Principles of Religious Moderation in Christianity: A Critical Analysis of Challenges and Social Realities - Anwar Ibrohim; Eko Yulianto; Rifki Rosyad; Moh. Dulkiah (Department of Social Studies Education, Faculty of Tarbiyah and Teacher Training, Datokarama State Islamic University of Palu, Central Sulawesi, Indonesia., 2026)
This study aims to analyze the concept of religious moderation within Catholic and Protestant Christian traditions, the challenges of its implementation in a pluralistic society, and the gap between theological teachings and the social practices of Christian communities. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation studies. The data were analyzed using an interactive analysis model involving data reduction, data presentation, and conclusion drawing, and were validated through source and method triangulation. The findings reveal that religious moderation in Christianity is rooted in the values of love, peace, tolerance, and respect for human dignity, yet it has transformed into a contextual, relational, and adaptive social practice. The study identified several challenges in implementing religious moderation, including identity exclusivism, identity politics, algorithmic radicalization in digital media, generational gaps, and performative moderation. In addition, the research found a gap between theological teachings on moderation and actual social practices due to the strong influence of social, cultural, political, and digital factors. The novelty of this study lies in the concepts of digital moderation, participatory moderation, relational moderation, symbolic moderation, and adaptive moderation. The study emphasizes that religious moderation should be realized through dialogical education, digital literacy, relational experiences, and interfaith cooperation in order to build an inclusive, harmonious, and socially just society.